2014
DOI: 10.1111/cobi.12362
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Evaluating the Umbrella Species Concept for Conserving and Restoring Landscape Connectivity

Abstract: Conserving or restoring landscape connectivity between patches of breeding habitat is a common strategy to protect threatened species from habitat fragmentation. By managing connectivity for some species, usually charismatic vertebrates, it is often assumed that these species will serve as conservation umbrellas for other species. We tested this assumption by developing a quantitative method to measure overlap in dispersal habitat of 3 threatened species-a bird (the umbrella), a butterfly, and a frog-inhabitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 40 publications
3
65
0
1
Order By: Relevance
“…Since 1989, bobcats have been protected in New Hampshire. In recent years, incidental sightings and road mortalities suggest that bobcats are becoming more abundant in New Hampshire (Broman et al 2014), similar to reports from other regions of North America (Roberts and Crimmins 2010).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Since 1989, bobcats have been protected in New Hampshire. In recent years, incidental sightings and road mortalities suggest that bobcats are becoming more abundant in New Hampshire (Broman et al 2014), similar to reports from other regions of North America (Roberts and Crimmins 2010).…”
Section: Introductionsupporting
confidence: 67%
“…However, more recent observations indicate that bobcats are re-colonizing portions of the state that contains dense road networks with substantial traffic volumes (Broman et al 2014). In comparison to other wide-ranging carnivores, such as coyotes (Canis latrans) and cougars (Felis concolor), Crooks (2002) indicated that bobcats are intermediate in their demographic responses to roads and they are able to persist in fragmented landscapes if there are habitat linkages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As species do not benefit uniformly from restoration interventions, a common approach is to design habitat protection and restoration of landscape connectivity based on an umbrella species concept (Breckheimer et al 2014). This concept holds that conservation of sufficient habitat for an animal with a very large home range should require areas large enough to provide sufficient area for most species that have smaller home ranges.…”
Section: Tools For Incorporating Biodiversity Into Systematic Restoramentioning
confidence: 99%
“…This concept holds that conservation of sufficient habitat for an animal with a very large home range should require areas large enough to provide sufficient area for most species that have smaller home ranges. Considering the potential for species movement within a landscape matrix, an umbrella species is one for which conservation or restoration of its dispersal habitat also facilitates dispersal of other target species (Breckheimer et al 2014). …”
Section: Tools For Incorporating Biodiversity Into Systematic Restoramentioning
confidence: 99%